Evaluation of surveillance of dengue fever cases in the public health centre of Putat Jaya based on attribute surveillance - Zumaroh Zumaroh (Universitas Airlangga, 2015)
Dengue Hemorrhagic Fever (DHF) is a public health problem in Putat Jaya Village which is endemic. Surveillance activities in the DHF control program are very important activities in controlling and monitoring the progress of the disease. The program is expected to reach IR 55 / 100,000 population. This study aims to evaluate the implementation of DHF case surveillance in the work area of the Public health center (PHC) of Putat Jaya based on 2013 surveillance attributes. This study is an evaluative study with descriptive study design. Data collection techniques with interviews and document studies. The informants in this study were PHC staff who specifically handled DHF cases and laboratory staff. The variables of this study are simplicity, flexibility, acceptability, sensitivity, positive predictive value, representativeness, timeliness, data quality, and data stability. The results showed that the existing case surveillance system is simplicity, acceptable, high Positive Predictive Value (PPV), high data stability, but low sensitivity, not representative, not timely, and has poor data quality. It can be seen from the Incidence Rate (IR) reaching 133 / 100,000 population. Surveillance activities at PHC of Putat Jaya in terms of the management of disease control programs are considered to have not been successful in reducing DHF IR. Therefore, it needs to increase cross-sector and cross-program collaboration, increase the number of surveillance personnel, and strengthen the DHF case reporting system.